Novel prognostic scoring system for autologous hematopoietic cell transplantation in multiple myeloma. (23rd October 2020) - Dhakal, Binod; D'Souza, Anita; Callander, Natalie; Chhabra, Saurabh; Fraser, Raphael; Davila, Omar; Anderson, Kenneth; Assal, Amer; Badawy, Sherif M.; Berdeja, Jesus; Cerny, Jan; Comenzo, Raymond; et al.
Abstract: We studied 2, 528 patients with upfront autologous haematopoietic cell transplantation (AHCT) for multiple myeloma (MM) from 2008–2017 to develop a prognostic model to predict outcomes. High‐risk cytogenetics included t(4;14), t(14;16), t(14;20), del13q on karyotype, del17p, +1q or 1pdel. A Cox model identified factors prognostic of progression/relapse in a training subset ( n = 1, 246). A weighted score using these factors was assigned to a validation cohort ( n = 774). Presence of high‐risk cytogenetics [hazard ratio, (HR) 1·68 (1·3–2·17)] and pre‐AHCT bone marrow plasma cells (BMPCs) ≥10% [1·68 (1·33–2·12)] were assigned 4 points each; albumin at diagnosis <3·5 g/dl [1·31 (1·07–1·61)] 2; standard risk cytogenetics 1, and no cytogenetics abnormality, BMPCs <10% at AHCT and albumin ≥3·5 g/dl at diagnosis 0 points each. A three‐category system with low risk (0–3), intermediate risk (4–8) and high risk (9–10) showed 3‐year progression‐free survival in the low vs. intermediate vs. high risk of 58% (95% CI: 52–63) vs. 49% (95% CI: 43–56) vs. 31% (95% CI: 12–51), P < 0.001 respectively, and 3‐year OS in low vs. intermediate vs. high risk of 88% (95% CI: 84–91) vs. 81% (95% CI: 76–86) vs. 64% (95% CI: 39–80); P < 0·001. Our prognostic scoring system can identify MM patients at risk for early relapse after AHCT.